Filter aid composite material

By combining the expanded grinding perlite and celite particles into composite particles using cross-linking binders, the existing filter aids have the problems of crystalline silica and high cost, and achieve high efficiency and low cost filtration effect.

CN119654191APending Publication Date: 2025-03-18IMERYS USA INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380056348.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-29
Filing Date
2023-07-26
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Existing filter aids have health and regulatory concerns in the filtration of beer and wine, and perlite-based filter aids are difficult to achieve target clarity, and the filter device is costly.

Method used

The mineral particles are bonded together by crosslinking binder to form composite particles to improve filtration performance by using composite particles containing crosslinking binder and expanded grinding perlite, celite particles and combinations.

Benefits of technology

The clarity of filter aids containing no crystalline silica, low-cost and standard DE-containing is achieved, significantly improving the filtration performance and solid retention capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005257106950000131
    Figure BDA0005257106950000131
  • Figure BDA0005257106950000141
    Figure BDA0005257106950000141
  • Figure HDA0005257106960000011
    Figure HDA0005257106960000011
Patent Text Reader

Abstract

A composition comprising a cross-linked binder and mineral particulates selected from the group consisting of: i) expanded ground perlite particulates having a D50 of from about 5 to about 40 microns; ii) diatomaceous earth particles having a D50 of from about 10 to about 50 microns; and combinations thereof; wherein the mineral particulates are bonded together by a cross-linking binder to form a composite particle wherein the composite particle has a D50 of about 20 to 100 microns.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a composition comprising composite particles and a cross-linking binder and a method for preparing the composition. The present disclosure also relates to a filter aid material comprising the composition and a method for filtering a liquid using the composition. Background Art

[0002] The filtration device typically includes a filter aid containing solid particles that improve the filtration efficiency. The filter aid is added to the suspension to be filtered or placed on the filter as a layer through which the liquid must pass.

[0003] Filter aids typically comprise materials derived from volcanic glass, such as perlite or pumice. Perlite filter aids are advantageously lightweight, inert, impart no taste or odor to the filtered liquid, and are virtually insoluble in mineral and organic acids at all temperatures.

[0004] Diatomaceous earth (DE) is another useful type of filter aid material and is a naturally occurring sand made from the fossilized remains of diatoms, a ubiquitous material. Diatomaceous earth based filter aids are typically used for primary clarification of beer and wine.

[0005] Due to the health and regulatory concerns that typically also exist regarding crystalline silica, customers in the beer and wine industry are increasingly seeking to move away from standard DE-based filter aids. Perlite-based filter aids can also suffer from issues with achieving target clarity. Cross-flow wine and beer filtration devices normally operate at a high cost. Therefore, it is desirable to provide a filter aid that is free of crystalline silica, low cost, and achieves the clarity of standard DE-containing filter aids. Summary of the invention

[0006] In the following description, certain aspects and embodiments will become apparent. It is contemplated that these aspects and embodiments in their broadest sense can be practiced without one or more features of the aspects and embodiments. It is also contemplated that these aspects and embodiments are merely exemplary.

[0007] According to a first aspect, there is provided a composition comprising composite particles comprising a crosslinked binder and mineral particles selected from the group consisting of: i) a particle having a D of about 5 to about 40 microns; 50 expanded ground perlite particles; ii) having a D of about 5 to about 40 microns 50 Diatomaceous earth particles; and combinations thereof; wherein the mineral particles are bound together by a cross-linking binder to form composite particles, wherein the composite particles have a D of about 20 to 100 microns 50, and wherein the binder is present in an amount of 0.01 wt % to 20 wt % based on the total weight of the composition, wherein the cross-linked binder is a reaction product of a polymer and a cross-linking agent, wherein the polymer is selected from the group consisting of a water-soluble synthetic polymer and a natural water-soluble polymer.

[0008] According to a second aspect, there is provided a filter-aid material comprising the composition according to the first aspect.

[0009] According to a third aspect, there is provided a method of filtering a liquid comprising contacting the liquid with the filter-aid material according to the second aspect.

[0010] According to a fourth aspect, there is provided a method of preparing a composition according to the first aspect.

[0011] The skilled person will appreciate that, except mutually exclusive situations, the features described in any one of the above aspects can be applied to any other aspects with necessary modifications. In addition, except mutually exclusive situations, any feature described herein can be applied to any aspect and / or combined with any other feature described herein. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Embodiments will now be described, by way of example only, with reference to the accompanying drawings, in which:

[0013] Figure 1 X-ray diffraction (XRD) spectra are depicted showing the crystallinity levels (peaks) of the comparative diatomaceous earth sample, the comparative perlite sample, and the novel composite sample of diatomaceous earth and expanded ground perlite.

[0014] Figure 2 Walton filtration graph plotting turbidity versus pressure rise showing turbidity for a comparative diatomaceous earth sample, a comparative perlite sample, and two novel composite samples of diatomaceous earth and expanded ground perlite.

[0015] Figure 3 Mercury porosimetry plots plotting intrusion volume versus pore size for a comparative diatomite sample, a comparative perlite sample, and two novel composite samples of diatomite and expanded ground perlite. DETAILED DESCRIPTION

[0016] Reference will now be made in detail to the exemplary embodiments illustrated in the accompanying drawings.

[0017] Surprisingly, it has been found that compositions comprising composite particles comprising a cross-linked binder and mineral microparticles selected from expanded ground perlite, diatomaceous earth microparticles, and combinations thereof achieve excellent filtration performance results.

[0018] Expanded ground perlite particles

[0019] Perlite typically contains the following components: silicon dioxide, aluminum oxide, sodium oxide, potassium oxide, iron oxide, magnesium oxide, calcium oxide, water and small amounts of other metallic elements.

[0020] The perlite particles of the present invention are in the form of expanded perlite. Typically, the expanded perlite includes one or more cells or portions of cells, wherein a cell is a void space partially or completely surrounded by a glass wall, typically formed by the expansion of a gas when the glass is in a softened state. A method for expanding perlite may include heating the perlite in air to a temperature of at least about 700° C., typically between 800° C. and 1100° C., in an expansion furnace. Exemplary methods for producing expanded perlite are described in US2006 / 0075930, the entire contents of which are incorporated herein by reference. The total volume of the expanded perlite is typically up to 20 times the total volume of the unexpanded material.

[0021] According to the invention, the perlite is ground after it has been expanded in an expansion furnace.

[0022] Unless otherwise specified, the particle size characteristics of the perlite particles mentioned herein are measured by methods employed in the field of laser scattering using a CILAS 1064L particle size analyzer such as supplied by CILAS (or by other methods that give substantially the same results). In the laser scattering technique, the size of particles in powders, suspensions, and emulsions can be measured using the diffraction of a laser beam based on the application of Fraunhofer and Mie theory. Such machines provide measurements and plots of the volume cumulative percentage of particles having a size less than a given esd value (referred to in the art as "equivalent spherical diameter" (esd)). The average particle size D 50 is the value of the esd of the particles determined in this way at which 50% by volume of the particles have an esd smaller than this value. 50 The equivalent spherical diameter of the value.

[0023] According to the present invention, the expanded ground perlite particles have a D of about 10 to about 50 microns. 50 , for example, a D of about 15 to about 45 microns, or about 20 to about 40 microns, or about 25 to about 35 microns 50 In certain embodiments, the expanded ground perlite particles have a D 50 .

[0024] In certain embodiments, the expanded ground perlite particles have a bulk density of about 0.05 g / cm 3 To about 0.20g / cm 3 , for example about 0.06 g / cm 3 To about 0.19g / cm 3, for example, about 0.07 g / cm 3 To about 0.18g / cm 3 , for example, about 0.08 g / cm 3 To about 0.17g / cm 3 , for example, about 0.09 g / cm 3 To about 0.16g / cm 3 , for example, about 0.10 g / cm 3 To about 0.15g / cm 3 , for example, about 0.11 g / cm 3 To about 0.14g / cm 3 , for example, about 0.12 g / cm 3 To about 0.13g / cm 3 .

[0025] In one embodiment, the perlite product is obtained from a commercially available perlite product. In another embodiment, at least one perlite product is available from Imerys Performance Materials Material.

[0026] Diatomaceous earth (DE) microparticles

[0027] Diatomaceous earth (DE) is derived from the remains of microscopic fossilized marine or freshwater algae. DE is typically employed as a filter aid. DE is known to have a complex and porous structure that is effective for trapping particulates during filtration.

[0028] The DE starting material can be DE in its crude form or can be subjected to one or more processing steps, such as physical or chemical modification. Physical modification methods include, but are not limited to, grinding, drying, and pneumatic classification. Chemical modification methods include, but are not limited to, silanization. Such modification methods are used to make the surface of DE more hydrophobic or hydrophilic using methods such as those described in US 3,915,735 and US 4,260,498, the contents of which are incorporated herein by reference.

[0029] DE typically contains about 80 to 90% silica with 2 to 4% alumina (primarily due to clay minerals) and 0.5-2% iron oxide.The types of DE available are well known to those skilled in the art.

[0030] Unless otherwise specified, the particle size characteristics of DE microparticles referred to herein are measured by the method discussed above for expanded ground perlite microparticles.

[0031] According to the present invention, DE particles have the following D 50: about 10 to about 50 microns, such as about 15 to about 45 microns or about 20 to about 40 microns or about 25 to about 35 microns. In certain embodiments, DE microparticles have a D of about 35 microns. 50 .

[0032] In certain embodiments, DE microparticles have a bulk density of about 0.05 g / cm 3 To about 0.46g / cm 3 , for example about 0.06 g / cm 3 To about 0.44g / cm 3 , for example, about 0.07 g / cm 3 To about 0.42g / cm 3 , for example, about 0.08 g / cm 3 To about 0.4g / cm 3 , for example, about 0.09 g / cm 3 To about 0.38g / cm 3 , for example, about 0.10 g / cm 3 To about 0.36g / cm 3 , for example, about 0.11 g / cm 3 To about 0.34g / cm 3 , for example, about 0.12 g / cm 3 To about 0.32g / cm 3 .

[0033] In one embodiment, the DE microparticles are commercially available diatomaceous earth products. In another embodiment, at least one natural diatomaceous earth microparticle is available from Imerys Performance Materials Material.

[0034] Adhesives

[0035] According to the present invention, a cross-linking binder is used to bind expanded ground perlite particles and / or DE together to form composite particles. The cross-linking binder is a reaction product of a polymer and a cross-linking agent, wherein the polymer is selected from a water-soluble synthetic polymer and a natural water-soluble polymer.

[0036] The binder of the present invention is a permanent binder. By this we mean that the binder is intended to remain in the composite particle product and provide structural strength to the composite particles, while being insoluble in the liquid to be filtered, for example when filtering beer.

[0037] In certain embodiments, the binder consists of a single type of polymer, or in certain embodiments, the binder comprises one or more polymers.

[0038] In certain embodiments, the polymer is selected from one or more of a water-soluble synthetic polymer and a natural water-soluble polymer. In certain embodiments, the polymer is a combination of these types of polymers.

[0039] In certain embodiments, the binder comprises a water-soluble synthetic polymer selected from, for example, polyvinyl alcohol (PVA), polyethylene glycol, urea-formaldehyde, polyacrylamide, microcrystalline cellulose, polyacrylates, acrylic acid / maleic acid copolymers, and polyvinyl pyrrolidone.

[0040] In certain embodiments, the binder comprises a natural water-soluble polymer such as xanthan gum, sodium alginate, potassium alginate, lignin sulfonate, locust bean gum, pectin, dextran, carrageenan, agar, xanthan gum, guar gum, gum arabic (gum arabic), cellulose ethers such as methylcellulose and ethylcellulose, starch, or starch-based derivatives.

[0041] According to the present invention, adhesive is a cross-linked adhesive, which is the reaction product of a polymer and a cross-linking agent. Cross-linking is the formation of chemical bonds between polymer chains to form a three-dimensional network of connected molecules. Polymer can be selected from the polymer list described above. Cross-linking agents are well known in the art and can be selected depending on the type of polymer. Cross-linking agents are not self-cross-linking polymers.

[0042] In certain embodiments, the cross-linking agent is an acid selected from one or more of the following:

[0043] (i) dicarboxylic acids, including oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, malic acid, tartaric acid, tartronic acid, aspartic acid, glutamic acid, fumaric acid, itaconic acid, maleic acid, callic acid, camphoric acid, phthalic acid and its derivatives containing at least one boron or chlorine atom, tetrahydrophthalic acid and its derivatives containing at least one chlorine atom, isophthalic acid, terephthalic acid, mesaconic acid and citraconic acid,

[0044] (ii) tricarboxylic acids including citric acid, tricarballylic acid, 1,2,4-butanetricarboxylic acid, aconitic acid, trimellitic acid, trimellitic acid and trimesic acid;

[0045] (iii) tetracarboxylic acids including 1,2,3,4-butanetetracarboxylic acid and pyromellitic acid;

[0046] (iv) polycarboxylic acids such as EDTA;

[0047] (v) unsaturated carboxylic acids including (ethyl) acrylic acid, crotonic acid, isocrotonic acid, maleic acid, cinnamic acid, 2-methylmaleic acid, fumaric acid, itaconic acid, 2-methylitaconic acid, α,β-methyleneglutaric acid and monoesters of unsaturated dicarboxylic acids, and the vinyl monomer is styrene optionally substituted by an alkyl group, a hydroxyl group or a sulfonyl group or styrene optionally substituted by a halogen atom, (meth)acrylonitrile, (meth)acrylamide optionally substituted by a C1-C10 alkyl group, alkyl (meth)acrylate, glycidyl (meth)acrylate, butadiene and vinyl ester

[0048] (vi) Inorganic acids such as boric acid and phosphoric acid.

[0049] In certain embodiments, the crosslinking agent is a carboxylic acid selected from dicarboxylic acids, tricarboxylic acids, tetracarboxylic acids, polycarboxylic acids, and unsaturated carboxylic acids. In certain embodiments, the carboxylic acid is a polycarboxylic acid such as citric acid or succinic acid. In certain embodiments, the carboxylic acid is an unsaturated carboxylic acid such as acrylic acid, methacrylic acid, and maleic acid.

[0050] In certain embodiments, the adhesive is the reaction product of polyvinyl alcohol and citric acid. Carboxylic acids are preferred crosslinking agent types because of their low toxicity and cost. Polyvinyl alcohol is also known to be non-toxic and biodegradable. The resulting crosslinked adhesive is insoluble in water and has low production cost.

[0051] In certain embodiments, the binder is present in an amount of about 0.1 wt % to about 40 wt % of the total wt % of the granules, or about 1 wt % to about 35 wt % of the total wt % of the granules, or about 5 wt % to about 30 wt % of the total wt % of the granules, or about 10 wt % to about 25 wt % of the total wt % of the granules, or about 15 wt % to about 20 wt % of the total wt % of the granules, or about 1 wt % to about 5 wt % of the total wt % of the granules.

[0052] In certain embodiments, the adhesive comprises a crosslinker in an amount of about 1 wt % to about 30 wt %, or such as about 2 wt % to about 25 wt %, or such as about 3 wt % to about 20 wt %, or such as about 4 wt % to about 15 wt %, or such as about 5 wt % to about 10 wt %, based on the total weight of the adhesive.

[0053] Composite particles

[0054] According to the present invention, mineral particles having the particle sizes described above are bound together using a binder selected from expanded ground perlite particles, diatomaceous earth particles and combinations thereof to form composite particles. The primary powder particles agglomerate to form larger multi-particle entities called composite particles.

[0055] In certain embodiments, the composite particles comprise or consist of expanded ground perlite particles and a binder. In certain embodiments, the composite particles comprise or consist of DE particles and a binder. In certain embodiments, the composite particles comprise or consist of expanded ground perlite particles and a binder. In certain embodiments, the composite particles comprise or consist of a blend of expanded ground perlite particles and DE particles and a binder.

[0056] The expanded ground perlite and / or DE particles are bound / agglomerated together by the binder, forming pores or otherwise referred to as interstitial void spaces between the particles. In some embodiments, the pores have a measurable intrusion volume, which can be measured by the methods explained in the Measurement Methods section below. In certain embodiments, the cumulative invasion volume is about 2.5 mL / g to about 4.5 mL / g, or about 2.6 mL / g, or about 2.7 mL / g, or about 2.8 mL / g, or about 2.9 mL / g, or about 3.0 mL / g, or about 3.1 mL / g, or about 3.2 mL / g, or about 3.3 mL / g, or about 3.4 mL / g, or about 3.5 mL / g, or about 3.6 mL / g, or about 3.7 mL / g, or about 3.8 mL / g, or about 3.9 mL / g, or about 4.0 mL / g, or about 4.1 mL / g, or about 4.2 mL / g, or about 4.3 mL / g, or about 4.4 mL / g, or about 4.5 mL / g. In certain embodiments, the median invasion volume is preferably about 3.5 mL / g.

[0057] The measured pore volume was advantageously found to be more than 25% greater than the typically used perlite or DE products. For example, a higher pore volume means that more volume per mass can pass through the filter. This allows for a greater solids holding capacity at an equivalent filter aid dosage.

[0058] In certain embodiments, the composite particle comprises expanded ground perlite particles and diatomaceous earth particles, and wherein at least one pore of the porous structure is filled with at least one unbound diatomaceous earth particle.

[0059] In certain embodiments, the ratio of expanded ground perlite to DE can be from about 5:1 to about 1:4, or from about 5:1 to about 1:3, or from about 5:1 to about 1:2, or from about 5:1 to about 1:1, or from about 5:1 to about 2:1, or from about 5:1 to about 1:3, or from about 4:1 to about 1:4, or from about 4:1 to about 1:3, or from about 4:1 to about 1:2, or from about 4:1 to about 1:1, or from about 4:1 to about 2:1, or from about 4:1 to about 1:3.

[0060] According to the present invention, by laser diffraction method, the composite particles have the following D50 : about 150 to about 2000 microns, for example, about 200 microns to about 1900 microns, or about 300 microns to about 1800 microns, or about 400 microns to about 1700 microns, or about 500 microns to about 1600 microns, or about 600 microns to about 1500 microns, or about 700 microns to about 1400 microns, or about 800 microns to about 1300 microns, or about 900 microns to about 1200 microns, or about 1000 microns to about 1600 microns. The composite particles may have a diameter of about 100 to about 1100 microns, or about 200 to about 600 microns, such as about 350 to about 550 microns, or about 400 to about 500 microns, or about 600 to about 1900 microns, such as about 700 to about 1800 microns, or about 800 to about 1600 microns, or about 900 to about 1500 microns, or about 1000 to about 1400 microns, or about 1100 to about 1300 microns. By laser, the composite particles may have a diameter of about 100 to about 1100 microns, or about 200 to about 600 microns, such as about 350 to about 550 microns, or about 400 to about 500 microns, or about 600 to about 1900 microns, such as about 700 to about 1800 microns, or about 800 to about 1600 microns, or about 900 to about 1500 microns, or about 1000 to about 1400 microns, or about 1100 to about 1300 microns. 50 : about 200 microns to about 1000 microns, or about 300 microns to about 900 microns, or about 400 microns to about 800 microns, or about 500 microns to about 700 microns.

[0061] In certain embodiments, the composite particles have a bulk density of about 0.1 g / cm 3 To about 0.50g / cm 3 , for example about 0.15 g / cm 3 To about 0.45g / cm 3 , for example, about 0.20 g / cm 3 To about 0.40g / cm 3 , for example, about 0.20 g / cm 3 To about 0.35g / cm 3 , for example about 0.25 g / cm 3 To about 0.30g / cm 3 .

[0062] The composite particles of the present invention may have a measurable BET surface area. The BET specific surface area refers to the surface area of ​​the particles of the composite particles per unit mass, which is measured according to the BET method by the amount of nitrogen adsorbed on the surface of the particles to form a monomolecular layer that completely covers the surface (measured according to the BET method, AFNOR standards X11-621 and 622 or ISO9277). The details of the BET specific surface area measurement method used in the preparation of the present application are described in the examples.

[0063] The composite particles may have a BET specific surface area of ​​not less than about 1.5 m 2 / g, for example not less than about 1.6 m 2 / g, or not less than about 1.7m 2 / g, or not less than about 1.8m 2 / g, or not less than about 1.9m 2 / g, or not less than about 2.0m 2 / g, or not less than about 2.5m 2 / g, or not less than about 3.0m 2 / g, or not less than about 5.0m 2 / g, or not less than about 10m 2 / g (e.g. 10.0m 2 / g), or not less than about 20m 2 / g (e.g. 11.0m 2 The composite particles may have a BET specific surface area of ​​not more than about 50 m 2 / g (e.g. 50.0m 2 / g), for example, not more than about 40 m 2 / g (e.g. 40.0m 2 / g), or not more than about 30m 2 / g (e.g. 30.0m 2 / g), or not more than about 20m 2 / g (e.g. 20.0m 2 / g), or not more than about 15m 2 / g (e.g. 15.0m 2 / g), or not more than about 12m 2 / g (e.g. 12.0m 2 / g), or not more than about 11m 2 / g (e.g. 11.0m 2 / g), or not more than about 10m 2 / g (e.g. 10.0m 2 / g), or not more than about 8.0m 2 / g, or not more than about 7.0m 2 / g, or not more than about 6.0m 2 / g. The composite particles may have a BET specific surface area, which may be about 1.5 m 2 / g to about 50m 2 / g (e.g. 50.0m 2 / g), for example, about 2m 2 / g to about 40m 2 / g (e.g. 40.0m 2 / g), or about 5m 2 / g to about 30m 2 / g (e.g. 30.0m 2 / g), or about 10m2 / g to about 20m 2 / g (e.g. 20.0m 2 / g).

[0064] In certain embodiments, the composite particles have an angle of repose of about 5° to about 35°, as measured by angle of repose (funnel method) using an EFT-01 powder flow tester; the composite particles have an absorption capacity of at least 150%, as measured using the Westinghouse method described in the experimental part of this article and using dioctyl adipate as the absorbate; and a dust content of less than 10, as measured by a dust analyzer DustmonRD 100.

[0065] The angle of repose of a material is the steepest angle of descent (angle of decent) or inclination relative to the horizontal plane, to which the material can be piled without collapsing. The morphology of the material affects the angle of repose. When bulk granular material is dumped onto a horizontal surface, a conical pile will be formed. The internal angle between the surface of the pile and the horizontal surface is called the angle of repose and is related to the density, surface area and shape of the particles and the friction coefficient of the material. Materials with low angles of repose form flatter piles than materials with high angles of repose. Therefore, smooth rounded sand grains cannot be piled as steeply as rough interlocking sand. The method for calculating the angle of repose is described in more detail in the experimental section below.

[0066] In certain embodiments, the angle of repose (of the dry product) is from about 5° to about 35°, such as from about 10° to about 30°, such as from about 15° to about 25°.

[0067] In certain embodiments, the composite particles have a low dust content (measured using a dust analyzer Dustmon RD 100 (available from The method for calculating the dust content values ​​is explained in more detail in the experimental part.

[0068] Composition

[0069] According to the present invention, there is provided a composition comprising composite particles. The composite particles are bonded together using a cross-linking binder.

[0070] In certain embodiments, the composition comprises additional inorganic mineral components. Examples of additional inorganic mineral components include natural or synthetic silicate or aluminosilicate materials, pumice, natural glass, cellulose, activated carbon, feldspar, nepheline syenite, sepiolite, zeolite and clay. Examples of clay minerals include halloysite, kaolinite and bentonite. Additional inorganic mineral components can be added in an amount of about 0.01 to about 10 parts, for example, about 0.5 to about 5 parts per part of expanded ground perlite and / or DE.

[0071] The composition is prepared by dry blending one or more mineral particles (dry powders of expanded ground perlite and / or DE and any other desired additional inorganic materials) and then spray drying the one or more mineral particles with a binder so that agglomerates form. The binder is first prepared by dissolving the binder ingredients in water.

[0072] When spray drying, the aqueous binder mixture is fed into the inlet of the spray dryer and sprayed onto the dry mixed mineral particles. An example of a suitable spray drying device is the Niro Minor spray dryer unit. This machine has a drying chamber with a diameter of 800 mm and a height of 600 mm based on a conical cylinder, and is equipped with an air-driven disc atomizer. The atomizer can be operated at a speed of 30,000 rpm.

[0073] The curing step (crosslinking step) is then carried out in a kiln at a temperature of about 80-120° C. The curing step is typically carried out for a period of time that allows the granules to dry and the binder to cure. After the curing step is carried out, the moisture content of the granules is less than about 5% by weight of the granules, such as less than about 3% by weight or less than about 2% by weight. The curing step is carried out for a period of time that allows the moisture content to reach the desired level as described above, and may take 12 hours or 8 hours or 4 hours.

[0074] This is a much lower temperature than that of standard production of DE, where kiln temperatures can exceed 1400°C. By avoiding the use of such high temperatures, and by keeping the temperature low, it is possible to prevent the formation of undesirable crystalline silica such as quartz or cristobalite. The presence of cristobalite in filter aids is generally undesirable because of its known potentially unhealthy properties at higher concentrations.

[0075] In certain embodiments, the total content of crystalline silica present in the composition is less than or equal to about 0.2 weight % of the total weight % of the composition. In certain embodiments, the composition comprises about 0 weight % to about 0.2 weight % of crystalline silica present in the composition, such as about 0.01 weight % to about 0.1 weight % of crystalline silica. In certain embodiments, the composition does not contain crystalline silica, which means that no crystalline silica is detected.

[0076] Method for measuring cristobalite content The measurement can be performed using techniques known to those skilled in the art, including the specific method described in WO 2010 / 042614.

[0077] Filter aid materials

[0078] According to the present invention, there is provided a filter-aid material comprising the composition described herein.The filter-aid composition may be formed into a sheet, pad, cartridge or other product for performing a filtering function.

[0079] The filter aids of the present invention can be used in various methods and compositions and various filtering methods. In certain embodiments, the filter aid material is applied to the filter membrane to protect it and / or to improve the clarity of the liquid to be filtered during the filtration process. In another embodiment, the filter aid composition is added directly to the beverage to be filtered to increase the flow rate and / or extend the filtration cycle. In another embodiment, the following method is provided: pre-coating at least one filter element with a filter aid material and contacting at least one liquid to be filtered with at least one coated filter element, or the liquid is to be used for body feeding or a combination of pre-coating and body feeding.

[0080] The filter-aid materials of the present invention can also be used in various filtering methods. In one embodiment, the filtering method comprises pre-coating at least one filter element with the composition of the present invention and contacting at least one liquid to be filtered with the at least one coated filter element. In such embodiments, contacting can include passing the liquid through the filter element. In another embodiment, the filtering method comprises suspending the filter-aid material in at least one liquid containing particles to be removed from the liquid, and then separating the filter-aid material from the filtered liquid.

[0081] Filter aid materials comprising the compositions of the present invention can also be used to filter various types of liquids. The skilled person will readily appreciate liquids that can be desirably filtered using a method comprising a filter aid comprising at least one diatomaceous earth product disclosed herein. In one embodiment, the liquid is a beverage. Exemplary beverages include, but are not limited to, vegetable-based juices, fruit juices, distilled spirits, and malt-based liquids. Exemplary malt-based liquids include, but are not limited to, beer and wine. In another embodiment, the liquid is a liquid that tends to form turbidity when cooled. In another embodiment, the liquid is a beverage that tends to form turbidity when cooled. In yet another embodiment, the liquid is beer. In yet another embodiment, the liquid is oil. In yet another embodiment, the liquid is edible oil. In yet another embodiment, the liquid is fuel oil. In another embodiment, the liquid is water, including but not limited to wastewater. In yet another embodiment, the liquid is blood. In yet another embodiment, the liquid is sake. In yet another embodiment, the liquid is a sweetener, such as corn syrup or molasses.

[0082] Example

[0083] Details of the comparative DE samples, comparative perlite samples, and novel composites of DE and expanded ground perlite used in the following examples are shown in Table 1 below.

[0084] Table 1

[0085]

[0086]

[0087] Example 1

[0088] Use 80g of expanded ground perlite ( 500, purchased from Imerys-sample C) to prepare a new composite material 1 (sample F), 80g of the expanded ground perlite and 20g of natural diatomaceous earth ( 615-Sample E) were placed together in a mixer (Kitchen Aid mixer) and the powders were dry mixed for 5 minutes at the lowest setting. 1.5g of polyvinyl alcohol (PVA) and 4.5g of citric acid were dissolved in 50g of water. The final % by weight of the adhesive was 6% by weight of the total composite particles. The adhesive composition was then sprayed onto the dry mixed powders and the composite particles were formed by agglomeration, taking 3 minutes to transfer all the solution to the Kitchen Aid mixer. The composite particles were then cured by heating in an oven at a temperature of 120°C for 85 minutes. The new composite material 1 was subjected to X-ray diffraction, Walton solid-liquid filtration and mercury porosity determination by the methods described below, and the results are shown in Figure 1 , 2 and 3.

[0089] Example 2

[0090] Use 66 g of expanded ground perlite ( 500, purchased from Imerys-sample C) to prepare a new composite material 2 (sample G), 66g of the expanded ground perlite and 33g of natural diatomaceous earth ( 615-Sample E) were placed together in a mixer (Kitchen Aid mixer) and the powders were dry mixed for 5 minutes at the lowest setting. 1.5g of polyvinyl alcohol (PVA) and 4.5g of citric acid were dissolved in 50g of water. The final % by weight of the adhesive was 6% by weight of the total composite particles. The adhesive composition was then sprayed onto the dry mixed powders and the composite particles were formed by agglomeration, taking 3 minutes to transfer all the solution to the Kitchen Aid mixer. The composite particles were then cured by heating in an oven at a temperature of 120°C for 85 minutes. The novel composite material 2 was subjected to Walton solid-liquid filtration and mercury porosity determination by the method described below, and the results are shown in Figure 2 and 3 middle.

[0091] When tested in a Walton filter (vertical tank, single horizontal blade, positive pressure, Ovaltine as suspended solids), the filtration performance of novel composites 1 and 2 demonstrated their competitiveness with standard grades of DE from the Lompoc facility. Novel composites 1 and 2, representing the inventive compositions described herein, demonstrated that the inventive compositions described herein exhibited the clarity of Hyflo (Sample A) with reduced pressure rise over time. Compared to perlite, the inventive compositions described herein significantly outperformed H500 (Sample C) in clarity at comparable pressures, and outperformed H200 (Sample D) in clarity at significantly reduced pressures, as shown in FIG. Figure 2 as displayed.

[0092] In addition to the filter performance, it is also important to Figure 3 As shown, note the increase in pore volume for new composites 1 and 2 compared to Hyflo (Sample A - 3.1 mL / g) and Standard Supercel (Sample B - 2.8 mL / g); Hyflo and Standard Supercel are each standard Lompoc DE grades. Typical calcined and flux-calcined DE grades have a pore volume of about 2.8 mL / g when measured in a mercury porosimeter. New composite 1 has a pore volume measured at 3.7 mL / g, a 25% increase over typical DE. This allows for greater solids holding capacity at equivalent filter aid dosage.

[0093] Measurement method

[0094] PSD laser

[0095] The particle size distribution (PSD) was determined using a Mastersizer 3500S from Malvern instruments.

[0096] D 50 is the value of the average particle size (d50) measured by laser diffraction (standard NFX-11-666 or ISO 13320-1), as described above and in the examples. Reference can be made to the article by G. Baudet and J. P. Na, Ind. Min. Mines et Carr. Les techn. 1990 June, July, pp. 55-61, which shows that the lamellarity index is related to the average ratio of the maximum size of the particles to their minimum size.

[0097] density

[0098] The bulk density of the sample is assessed by measuring the volume of the sample into the test tube and comparing the volume of the sample to the mass of the sample.

[0099] Specific surface area (SSA-BETm 2 / g)

[0100] The BET specific surface area is determined using a method based on standard NF X 11-621 entitled “Determination of the mass (surface) area of ​​powders by gas adsorption - BET method - Volume measurement by nitrogen adsorption at low temperatures” (Determination of the mass area (specific surface area) of powders by gas adsorption - BET method - Volume measurement by nitrogen adsorption at low temperatures).

[0101] The method uses a Micromeritics measuring device (available from Micromeritics Instrument Corp., USA) including a vacuum pump, a VacPrep 061 degassing section, a Tristar 3000S measuring section and a sample holder, a Mettler AG204 balance with an accuracy of 0.1 mg, a Dewar flask, a nitrogen adsorption gas, and a helium carrier gas.

[0102] Weigh the sample near the empty sample holder (to 0.1 mg accuracy) and record its mass M0 in g. Then use a funnel to introduce the previously homogenized powder sample into the sample holder. Leave enough space (dead volume) between the sample and the top of the sample holder to allow the gas to circulate freely. The sample holder is placed in one of the degassing stations and degassed at a primary vacuum of 10 Pa for about 20 minutes at 250°C. After degassing, a sufficient volume of nitrogen is added to the sample holder to avoid the introduction of air during the transfer of the sample holder from the degassing station to the measuring station.

[0103] The sample holder is then attached to the measurement station and a Dewar containing liquid nitrogen is placed around the sample holder. The BET measurement is started using the device control software. The device then automatically performs the following operations:

[0104] · Vacuum remove the nitrogen gas introduced into the sample holder for transfer;

[0105] Leakage test;

[0106] Add helium carrier gas;

[0107] Measure dead volume at ambient temperature;

[0108] ·Measure the cold dead volume using liquid nitrogen;

[0109] Helium vacuum removal;

[0110] Leakage test;

[0111] Add nitrogen at 950 mm Hg and measure the saturation pressure; and

[0112] Get analysis values.

[0113] The instrument's data acquisition and processing software plots the converted BET line from the 5 measured adsorption points. Remove the Dewar flask and then the sample holder. Allow the apparatus to return to ambient temperature and then weigh the sample again near the sample holder (to an accuracy of 0.1 mg), and record the weight as M2 in g. Calculate the mass M (in g) of the sample of the test portion according to the following:

[0114] M=M2-M0

[0115] Then the value M is introduced into the automatic calculation to m 2 Software calculation program for the BET specific surface area of ​​samples measured in g / g.

[0116] Porosity

[0117] Porosity is the percentage of interstitial void space in a particle. It is calculated using the following formula:

[0118] Φ=V v / V T

[0119] Where Φ is the porosity, V v is the void volume, V T is the total volume.

[0120] Porosity was measured using mercury porosimetry, which characterizes porosity by forcing mercury into the pores. The method used herein to measure porosity is the standard test for mercury porosimetry as set forth in ASTM D4404-18.

[0121] Angle of repose

[0122] The angle of repose was measured using a manual powder flow tester (EFT-01) according to ISO 8398: 1989. The angle of repose was calculated as follows:

[0123] θ=tan -1 h / r

[0124] where θ is the angle of repose, h is the height of the conical pile in cm, and r is the radius in cm.

[0125] The complementary measurement of the angle of repose is the dynamic angle of repose (or flow angle) measured using a Granudrum. The GranuDrum instrument (available from GRANUTOOLS TM The automatic powder flowability measurement technique is based on the principle of a rotating drum. The drum is a horizontal cylinder with transparent side walls and is half filled with powder sample.

[0126] The drum rotates around its axis at an angular velocity varying from 2 to 70 rpm. In this case, the angular velocity was measured at 10 rpm and a CCD camera captured a number of snapshots. For the measured rotational speeds, the dynamic cohesion index was measured from the interface fluctuations and the flow angle, also called "dynamic repose angle" in the literature, was calculated from the average interface position. Low values ​​of the flow angle correspond to excellent flowability.

[0127] XRD

[0128] X-ray diffraction is used to identify and quantify mineral species, such as crystalline and inorganic species. The sample holder is filled with about 1 gram of powder sample and placed in the XRD machine, i.e., using a Ge monochromator to generate CuK α The scanning range in 2θ angle was 2° to 70°.

[0129] Crystalline silica ("CS") has a primary major peak at or near 21.5°. Hyflo shows a distinctive primary peak of CS at low count intensities as well as characteristic secondary and tertiary peak signals. Perlite (H500) and novel composites 1 and 3 have very weak signals in this range even at very high count intensities.

[0130] Walton

[0131] 4 L of solid suspension was prepared using Ovaltine (consisting of 5 g / L Ovaltine in deionized water) as a model solid solution. It was hydrated for 45 minutes. A pressure vessel was filled with deionized water and at 20 cm 2 A Hyflo pre-coat (2.0 g in 50 mL) was prepared on a stainless steel Dutch weave sieve. This pre-coat was added at a flow rate of 150 mL / min. Once applied, the turbidity was monitored by measuring the NTU using a turbidimeter with a target NTU < 1. After 45 minutes of Ovaltine hydration, the respective sample filter aids were added to 4 L of the solid suspension at a concentration of 2 g / L. The Ovaltine and filter aid suspension is referred to as the body feed. The body feed was injected into the pressure vessel at 60 mL / min for 30 minutes. The pressure and turbidity were monitored every minute. For Figure 2In the Walton plot, the pressure rise from 10 to 20 minutes is collected and the turbidity is reported at 20 minutes.

[0132] The perlite grades (H500 and H200) showed higher turbidity relative to the diatomaceous earth (Hyflo and Standard Supercel) and relative to the new composites 1 and 2. The perlite grades showed higher pressure rise relative to the new composites 1 and 2. The diatomaceous earth grades showed higher pressure rise relative to the new composites 1 and 2. In addition, the Hyflo turbidity was higher compared to the new composites 1 and 2, all as shown in Figure 2. Figure 2 as displayed.

Claims

1. A composition comprising composite particles comprising a cross-linked binder and mineral particles selected from the group consisting of: i) having a D of about 5 to about 40 microns; 50 ii) having a D of about 10 to about 50 microns 50 Diatomaceous earth particles; and combinations thereof; wherein the mineral particles are bonded together by the cross-linking binder to form composite particles, wherein the composite particles have a D of about 20 to 100 microns. 50 , and wherein the binder is present in an amount of 0.1 wt % to about 40 wt % based on the total weight of the composition, wherein the cross-linked binder is a reaction product of a polymer and a cross-linking agent, wherein the polymer is selected from the group consisting of a water-soluble synthetic polymer and a natural water-soluble polymer.

2. The composition according to claim 1, wherein the crosslinking agent is an acid selected from one or more of the following: (i) dicarboxylic acids, including oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, malic acid, tartaric acid, tartronic acid, aspartic acid, glutamic acid, fumaric acid, itaconic acid, maleic acid, callic acid, camphoric acid, phthalic acid and its derivatives containing at least one boron or chlorine atom, tetrahydrophthalic acid and its derivatives containing at least one chlorine atom, isophthalic acid, terephthalic acid, mesaconic acid and citraconic acid, (ii) tricarboxylic acids including citric acid, tricarballylic acid, 1,2,4-butanetricarboxylic acid, aconitic acid, trimellitic acid, trimellitic acid and trimesic acid; (iii) tetracarboxylic acids including 1,2,3,4-butanetetracarboxylic acid and pyromellitic acid; (iv) polycarboxylic acids such as EDTA; (v) unsaturated carboxylic acids including (ethyl) acrylic acid, crotonic acid, isocrotonic acid, maleic acid, cinnamic acid, 2-methylmaleic acid, fumaric acid, itaconic acid, 2-methylitaconic acid, α,β-methyleneglutaric acid and monoesters of unsaturated dicarboxylic acids, and the vinyl monomer is styrene optionally substituted by an alkyl group, a hydroxyl group or a sulfonyl group or styrene optionally substituted by a halogen atom, (meth)acrylonitrile, (meth)acrylamide optionally substituted by a C1-C10 alkyl group, alkyl (meth)acrylate, glycidyl (meth)acrylate, butadiene and vinyl ester (i) Inorganic acids such as boric acid and phosphoric acid.

3. The composition of claim 2, wherein the binder is a reaction product of polyvinyl alcohol and an acid.

4. The composition of claim 3, wherein the acid is citric acid. 5 . The composition of claim 1 , wherein the composite particles are bonded by the cross-linking binder and form a porous structure comprising pores having a pore volume of 2.5 to 4.5 mL / g.

6. The composition of claim 5, wherein the composite particles comprise expanded ground perlite particles and diatomaceous earth particles.

7. The composition of claim 6, wherein at least one pore of the porous structure is filled with at least one unbound diatomaceous earth particle.

8. The composition according to claim 1, comprising: An angle of repose of about 5° to about 30° as measured by Angle of Repose (Funnel Method) using an EFT-01 Powder Flow Tester; An absorbent capacity of at least 150% as measured using the Westinghouse method described herein and utilizing dioctyl adipate as the absorbate; and Dust content of less than 10, as measured by dust analyzer Dustmon RD 100.

9. The composition of claim 1, wherein the expanded ground perlite particles have a D 50 .

10. The composition of claim 1, wherein the diatomaceous earth particles have a D 50 .

11. The composition of claim 1, wherein the composite microparticles have a D of about 30 to about 40 microns. 50 .

12. The composition of claim 1, wherein the composite particles comprise expanded ground perlite microparticles and diatomaceous earth microparticles in a ratio of 5:1 to 1:

4.

13. The composition of claim 1, wherein the crystalline silica present in the composition is less than or equal to about 0.2 weight percent of the total weight percent of the composition.

14. A filter-aid material comprising the composition according to claim 1.

15. A method of filtering a liquid, the method comprising contacting the liquid with the filter-aid material according to claim 12.

16. A method of preparing a composition comprising composite particles, the method comprising: (a) spray drying mineral particles with a cross-linking binder to form composite particles, wherein the mineral particles are selected from: i) having a D of about 5 to about 40 microns 50 ii) having a D of about 10 to about 50 microns 50 Diatomaceous earth particles; and combinations thereof, wherein the composite particles have a D of about 20 to 100 microns. 50 , and wherein the binder is present in an amount of 0.01 wt % to 20 wt % based on the total weight of the composition, wherein the cross-linked binder is a reaction product of a polymer and a cross-linking agent, wherein the polymer is selected from the group consisting of a water-soluble synthetic polymer and a natural water-soluble polymer; and (b) Curing the composition in a kiln.

17. The method of claim 14, wherein the curing step is performed in a kiln at a temperature of 80-300°C.

18. The method of claim 15, wherein the curing step is performed for 4 to 12 hours.

Citation Information

Patent Citations

  • Micronized perlite filler product

    US20060075930A1

  • Process for preparing modified silicic fillers

    US3915735A

  • Silane coated silicate minerals and method for preparing same

    US4260498A

  • Diatomaceous earth products, processes for preparing them, and methods of their use

    WO2010042614A1